Penerapan Metode Pemberian Tugas Non-Tatap Muka Oleh Guru Di Masa Pandemi Covid-19 Pada Pelajaran Seni Budaya Di SMP Negeri 3 Padang - Endri Astuti; Yos Sudarman (FBS Universitas Negeri Padang, 2021)
This research aims to describe the use of non-face-to-face tasking methods by teachers in Cultural Arts lessons at SMP Negeri 3 Padang, where research problems are backgrounded by the problem of learning cultural arts (music) during the covid-19 pandemic, in unisono singing lessons. The study of the theory that is the cornerstone of scientific thinking in this research relates to education, learning and learning; learning methods, task-giving methods, non-face-to-face distance learning and Cultural Arts learning. While the research methods used are of a type of quantitative research with a descriptive approach to analysis. Based on the results of two meetings, researchers can explain that the implementation of non-face-to-face tasking methods of cultural arts (music) subjects with unisono singing material grades VII-3 in SMP Negeri 3 Padang is the best choice by teachers to continue to carry out kbm music art in times of pandemic. Although the use of online learning properly through video conferences, due to the limitations of the facilities and quotas available on the part of students and parents, this online learning activity was replaced by the provision of non-face-to-face assignments using the WA app. With this method of learning, although not online, it can overcome various music learning activities that remained carried out during the pandemic. With this kind of learning, the goal of achieving the goal of learning is only in the field of appreciation towards singing unisono only, because the target goal of learning practice is difficult to achieve.